A Study on the Political Value of Rallies: Exploring the Nexus between Political Activism and Economic Gains (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The recent climate of competition has led to the emergence of sizable rent-seeking professional leaders. They calculate the returns on the political and economic investments made, which is not confined to a zero-sum game of winning elections. There are pay-offs even when one loses an election. Being in politics, a party activist has a distinct identity that could reap dividends in the form of prestige, status and accessibility. These could be converted to pecuniary benefits. Parties look like business firms in a political market. India having a population of a billion and a quarter and an electorate of 814 million (2014) - is the world's largest democracy and this democratic system stands in marked contrast since independence.